Survei Minat terhadap Cabang Olahraga Rugby di SMA Negeri 2 Sukoharjo - Susanto, Falih Zahran Ramadhany; Sistiasih, Vera Septi (Lembaga Yasin AlSys, 2023)
This research is motivated by the unpopularity of Rugby at SMA Negeri 2 Sukoharjo. This study aims to determine students' interest in the Rugby Sports Branch at SMA Negeri 2 Sukoharjo. This study uses quantitative methods, data collection techniques used in this study using surveys in the form of distributing questionnaires to the population studied so that conclusions can be drawn in the form of statistical data. The sample used in this study were students from SMA Negeri 2 Sukoharjo, totaling 50 students using a purposive sampling population. The results showed that after testing the validity of the data, there were 87.5% valid data. While the results of the reliability test found that the Cronbach's Alpha value was above 0.50, where the Cronbach's Alpha value was 0.749 which means it has a reliability value. Then it can be concluded from the results of the description that students of SMA Negeri 2 Sukoharjo have the greatest interest in participating in Rugby from the encouragement of the students' parents.